Hepatitis C virus targets the interferon-α JAK/STAT pathway by promoting proteasomal degradation in immune cells and hepatocytes - Stevenson, Nigel John; Bourke, Nollaig M.; Ryan, Elizabeth J.; Binder, Marco; Fanning, Liam; Johnston, James A.; Hegarty, John E.; Long, Aideen; O'Farrelly, Cliona (FEBS letters, 2013)
JAK/STAT signalling is essential for anti-viral immunity, making IFN-α an obvious anti-viral therapeutic. However, many HCV+ patients fail treatment, indicating that the virus blocks successful IFN-α signalling. We found that STAT1 and STAT3 proteins, key components of the IFN-α signalling pathway were reduced in immune cells and hepatocytes from HCV infected patients, and upon HCV expression in Huh7 hepatocytes. However, STAT1 and STAT3 mRNA levels were normal. Mechanistic analysis revealed that in the presence of HCV, STAT3 protein was preferentially ubiquitinated, and degradation was blocked by the proteasomal inhibitor MG132. These findings show that HCV inhibits IFN-α responses in a broad spectrum of cells via proteasomal degradation of JAK/STAT pathway components.
Available online 12 April 2013
Gesehen am 22.02.2022